Green emission fluorophores in eyes with atrophic age-related macular degeneration: a colour fundus autofluorescence pilot study. Issue 6 (25th September 2017) - Borrelli, Enrico; Lei, Jianqin; Balasubramanian, Siva; Uji, Akihito; Cozzi, Mariano; Sarao, Valentina; Lanzetta, Paolo; Staurenghi, Giovanni; Sadda, SriniVas R
Abstract : Background/Aims: To investigate the presence of short-wave fluorophores within regions of age-related macular degeneration (AMD)-associated macular atrophy (MA) area. Methods: This is a prospective, observational, cross-sectional case series. 25 eyes (18 patients) with late AMD and clinically identified MA were enrolled. Eyes were imaged using a confocal light-emitting diode blue-light fundus autofluorescence (FAF) device (EIDON, CenterVue, Padua, Italy) with 450 nm excitation wavelength and the capability for 'colour' FAF imaging, including both the individual red and green components of the emission spectrum. To produce images with a high contrast for isolating the green component, the red component was subtracted from the total FAF image. The main outcome measure was the presence of green emission fluorescence component (GEFC) within the MA area. Volume spectral domain optical coherence tomography (SD-OCT) scans were obtained through the macula and the OCT was correlated with the MA lesions identified on the FAF images, including regions of increased GEFC. Results: Of the investigated eyes, 11 out of 25 (44.0 %) showed the absence of GEFC in the MA area, whereas 14 eyes (56.0%) were characterised by GEFC within the MA area. The presence and distribution of GEFC in the MA area correlated with the presence of hyper-reflective material over Bruch's membrane on the corresponding SD-OCT scans. Conclusion: Short-wave fluorophores, which contribute to the GEFC, are present in the MA area and appear to correspond to residual debris or drusenoid material. Short-wavelength fluorophores revealed by colour FAF imaging may warrant further study.